Graphene‐Based Mixed‐Dimensional van der Waals Heterostructures for Advanced Optoelectronics. Issue 37 (10th July 2019) - Zhang, Zheng; Lin, Pei; Liao, Qingliang; Kang, Zhuo; Si, Haonan; Zhang, Yue
Abstract: Although the library of 2D atomic crystals has greatly expanded over the past years, research into graphene is still one of the focuses for both academia and business communities. Due to its unique electronic structure, graphene offers a powerful platform for exploration of novel 2D physics, and has significantly impacted a wide range of fields including energy, electronics, and photonics. Moreover, the versatility of combining graphene with other functional components provides a powerful strategy to design artificial van der Waals (vdWs) heterostructures. Aside from the stacked 2D–2D vdWs heterostructure, in a broad sense graphene can hybridize with other non‐2D materials through vdWs interactions. Such mixed‐dimensional vdWs (MDWs) structures allow considerable freedom in material selection and help to harness the synergistic advantage of different dimensionalities, which may compensate for graphene's intrinsic shortcomings. A succinct overview of representative advances in graphene‐based MDWs heterostructures is presented, ranging from assembly strategies to applications in optoelectronics. The scientific merit and application advantages of these hybrid structures are particularly emphasized. Moreover, considering possible breakthroughs in new physics and application potential on an industrial scale, the challenges and future prospects in this active research field are highlighted. Abstract : Graphene offers a powerful platform for exploration of novel 2D physics, and has had a significant impact on a wide range of fields including energy, electronics, and photonics. Hybridization of graphene with other materials, 2D and otherwise, may provide a promising solution to graphene's intrinsic weakness and allow full exploitation of its potential.